An annotated type catalogue of freshwater sculpins (Cottoidei) described by Lev Berg - Sideleva, Valentina G.; Zhidkov, Zakhar V. (Zootaxa, 2021)
The catalog is represented by type specimens of species and subspecies of cottoid fishes described by Lev S. Berg which are kept in the ichthyological collection of the Zoological Institute of Russian Academy of Sciences, St. Petersburg, Russia. The collection contains type specimens representing 14 taxa (species and subspecies) of the two families Abyssocottidae and Cottidae. In total, Lev S. Berg described one family, Cottocomephoridae, five genera, Abyssocottus, Asprocottus, Baicalocottus, Batrachocottus and Cottinella, 10 species and four subspecies. Four genera and 10 species are currently considered valid.